2019
DOI: 10.3390/coatings9010025
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Synthesis and Characterization of Aqueous Hybrid Silicone-Acrylic and Acrylic-Silicone Dispersions and Coatings. Part I

Abstract: The objective of the study was to investigate the effect of the method of synthesis on properties of aqueous hybrid silicone-acrylic (SIL-ACR) and acrylic-silicone (ACR-SIL) dispersions. SIL-ACR dispersions were obtained by emulsion polymerization of mixtures of acrylic and styrene monomers (butyl acrylate, styrene, acrylic acid and methacrylamide) of two different compositions in aqueous dispersions of silicone resins synthesized from mixtures of silicone monomers (octamethylcyclotetrasiloxane, vinyltriethoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It was observed that the T g of the PAcr part of the Si‐PAcr/PB latex films with different silicone dosages showed a decreasing trend. Compared with the PAcr/PB latex film, the T g values of the Si‐PAcr/PB‐20/1, Si‐PAcr/PB‐30/1 and Si‐PAcr/PB‐50/1 hybrid latex films decreased to 10.46, 8.46 and 8.32°C, respectively, which was a result of the plasticising effect of siloxane 31,37 . Those lower values of T g implied high flexibility and mobility of the copolymer chain.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…It was observed that the T g of the PAcr part of the Si‐PAcr/PB latex films with different silicone dosages showed a decreasing trend. Compared with the PAcr/PB latex film, the T g values of the Si‐PAcr/PB‐20/1, Si‐PAcr/PB‐30/1 and Si‐PAcr/PB‐50/1 hybrid latex films decreased to 10.46, 8.46 and 8.32°C, respectively, which was a result of the plasticising effect of siloxane 31,37 . Those lower values of T g implied high flexibility and mobility of the copolymer chain.…”
Section: Resultsmentioning
confidence: 96%
“…So, it is reasonable to consider if precursor silane can be directly introduced to the PAcr chains and whether the formation of a much more compatible and high‐performance hybrid material should be expected. Although PAcr‐silicone combining resins have been studied previously, and the properties of such hybrid dispersions, coatings and films investigated by Kozakiewicz et al, 29–31 research on pigment hybrid films is very limited. The influence of the molecular structure of PAcr‐silicone copolymer on the textile pigment printing performance of waterborne self‐adhesive hybrid pigment is unknown and needs to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, enhancements in corrosion hinderance and mechanical strength have been attained. These enhancements in properties are demonstrated in incremental cohesive and adhesive behaviors of the nano-architecture attributed to appropriate dispersion of nanofillers in the matrix [40] , [41] , [42] , [43] . Additionally, both anti-scratch and anti-wear resistances are enhanced with increasing nanoparticle weight percent in polymeric matrices [44] .…”
Section: Pnc Coatings Properties and Classificationmentioning
confidence: 99%
“…In contrast, acrylic systems are much less permeable to gases and vapors, which causes unfavorable sealing of the building material [32]. In order to achieve high surface hydrophobicity and water resistance combined with good water vapor permeability hybrid silicone-acrylic dispersions can be used [33].…”
Section: Synthetic Polymersmentioning
confidence: 99%